KEMANTAPAN AGREGAT SETELAH APLIKASI BIOCHAR DI TANAH LEMPUNG BERPASIR PADA PERTANAMAN JAGUNG DI LAHAN KERING KABUPATEN LOMBOK UTARA - Suwardji Suwardji; W.H. Utomo; Sukartono Sukartono (BUANA SAINS, 2012)
Evaluation of changeable agregat stability was done almost one year after application of biochar during rainy season 2010/2011 of three cyles maize planting in dryland of North Lombok. Three points of undisturbed soil samples in depth 0-20 cm were collected one month after maize harvest of previously addedbiochar land. Site of soil sample was treated by application of organic matter consisting of biochar coconut hust (BTK), biochar cow manure (BKS), one season application of manure (PKA), each season aplication of manure (PkB) and control (K : without soil amandement). The results showed that after one year application of biochar increased the limited value stability of soil agregat. The value was 61,37% and 61,18% for BTK and BTS, respectivel, while for treatment of PkA, PkB dan control gave value 58,44%, 66,62% and 57,11%. Increasing stability of soil agregat after application of organic soil amandement positively correlated with i the increase of soil organic and water soil retention. Therefore, experiment suggested that modification is needed for application biochar and manure in long period of maize cropping pattern in dryland of North Lombok